Для простоты b2=х
b3=х*q
b4=х*q*q
система уравнений
х+х*q=-12
х*q*q-х=48
х(1+q)=-12
х(q^2-1)=48
-12
х=--------------
1+q
48
х=-------------
q^2-1
-12 48
--------------=------------
1+q q^2-1
-12 48
--------------=------------ домножим на (1+q)
1+q (q-1)(q+1)
-12 48
--------------=------------ разделим на 12
1 (q-1)
-1 4
--------------=------------
1 (q-1)
4
--------------=-1
(q-1)
(q-1)=-4
q=-4+1=-3 -знаменатель прогрессии
подставим в х(1+q)=-12
х(1+(-3))=-12
-2х=-12
х=6- это b2
b1=6: -3= -2
S5=-2*((-3)^5-1)/(-3-1)=-2*(-243-1)/(-4)=(-243-1)/2=-244/2=-122